Occurrence and potential transfer of mycotoxins in gilthead sea bream and Atlantic salmon by use of novel alternative feed ingredients - Nácher-Mestre, Jaime; Serrano, Roque; Beltrán, Eduardo; Pérez-Sánchez, Jaume; Karalekas, Vasileios; Hernández Hernández, Félix; Berntssen, Marc H. G. (Chemosphere, 2015)
Plant ingredients and processed animal proteins (PAP) are suitable alternative feedstuffs for fish feeds in aquaculture practice, although their use can introduce contaminants that are not previously associated with marine salmon and gilthead sea bream farming. Mycotoxins are well known natural contaminants in plant feed material, although they also could be present on PAPs after fungi growth during storage. The present study surveyed commercially available plant ingredients (19) and PAP (19) for a wide range of mycotoxins (18) according to the EU regulations. PAP showed only minor levels of ochratoxin A and fumonisin B1 and the mycotoxin carry-over from feeds to fillets of farmed Atlantic salmon and gilthead sea bream (two main species of European aquaculture) was performed with plant ingredient based diets. Deoxynivalenol was the most prevalent mycotoxin in wheat, wheat gluten and corn gluten cereals with levels ranging from 17 to 814 and μgkg-1, followed by fumonisins in corn products (range 11.1-4901μgkg-1 for fumonisin B1+B2+B3). Overall mycotoxin levels in fish feeds reflected the feed ingredient composition and the level of contaminant in each feed ingredient. In all cases the studied ingredients and feeds showed levels of mycotoxins below maximum residue limits established by the Commission Recommendation 2006/576/EC. Following these guidelines no mycotoxin carry-over was found from feeds to edible fillets of salmonids and a typically marine fish, such as gilthead sea bream. As far we know, this is the first report of mycotoxin surveillance in farmed fish species. © 2015 Elsevier Ltd. This work has been (partly) funded under the EU Seventh Framework Programme by ARRAINA Project 288925: Advanced Research Initiatives for Nutrition and Aquaculture. The views expressed in this work are the sole responsibility of the authors and do not necessarily reflect the views of the European Commission. The authors also acknowledge the financial support (partly) of the project SAFE-PAP, Research Council Research and ...